INTELLIGENT SYSTEM OF TRAFIC LIGHT CONTROL WITH DYNAMIC CHANGE PHASES OF TRAFFIC FLOWS ON UNCONTROLLED INTERSECTIONS - Мoroz B. I.; Alekseieiev M. O.; Shvachych G. G.; Pasichnik A. M.; Miroshnichenko S. V. (World Science, 2018)
There was method of making an effective system of traffic-light control of the traffic through the intersections in one direction according to which the phase coefficients for each cycle of traffic-light control are computed in real-time using the data of traffic intensity detected by transport detectors. Thus, the built-in traffic control system will be dynamically adapted to the change in the intensity of traffic flows, and the structure of the cycle and its duration will be changed taking into account the parameters of the traffic flow at the intersection. Accordingly, the traffic light cycle, where each cycle has the minimum required duration, will be most effective and will ensure uninterrupted traffic, the lack of traffic jams and the convenience for the pedestrian crossings.